Exploring the therapeutic effect of Calmcube play on emotional well-being in hospitalized preschool-aged children - Rahayu, Devia Sri; Mariani, Dini; Rosuliana, Novi Enis; Herliana, Lia (Poltekkes Kemenkes Yogyakarta, 2025)
Hospitalization can trigger significant anxiety in preschool children (ages 3–6) due to separation from familiar environments, invasive medical procedures, and limited emotional coping strategies. Excessive anxiety during hospitalization may hinder recovery and negatively affect emotional development. Play therapy is a widely recommended non-pharmacological approach to reduce pediatric anxiety. CalmCube is an innovative play therapy tool designed to engage children's cognitive and emotional responses through interactive, age-appropriate activities. This study aimed to evaluate the effectiveness of CalmCube play therapy in reducing anxiety among hospitalized preschool children. A quasi-experimental study using a pretest-posttest control group design was conducted at Dr. Soekardjo Hospital from October to December 2024. A total of 38 preschool-aged children (3–6 years) were selected through purposive sampling and assigned to intervention (n = 19) and control (n = 19) groups. Anxiety levels were measured using the Preschool Anxiety Scale (PAS) before and after the intervention. Data were analyzed using paired and independent sample t-tests. In the intervention group, the mean anxiety score decreased significantly from 37.10 (SD = 19.83) to 29.21 (SD = 17.57) after CalmCube therapy (p = 0.000). In contrast, the control group showed a negligible reduction from 44.78 to 43.94 (p = 0.076). Between-group analysis also revealed a statistically significant difference in post-intervention anxiety levels (p = 0.016), confirming the effectiveness of CalmCube therapy. CalmCube play therapy significantly reduced anxiety in hospitalized preschool children and can be implemented as a non-pharmacological nursing intervention to improve children's psychological well-being during hospitalization. Integrating structured play therapy into pediatric care protocols may enhance emotional resilience and recovery outcomes in young patients.